Experimental Study on Vibration Level of Automotive Flexibel Wiper System - Salim, Mohd Azli; Abd Munir, Fudhail; Noordin, Aminurrashid (Universiti Teknikal Malaysia Melaka, 2012)
This study represent the experimental study of automotive flexible wiper system by using analytical and test rig analysis. In order to doing so, conservation and newtonian approach is applied to develop two dimensional of differential equation for the system. In analytical approach, the results have shown in time and frequency domain, which are represented the annoying noise and vibration level during the system operate. These results were compared with experimental study using Fast Fourier Transform (FFT) technique. In this comparison, these two results have shown a corelation data and it is believed trustworthy to make a further analysis. The percentage of corelation is more than 97 percent.